STUDI KUALITATIF GETARAN UMUM YANG TERJADI PADA KAPAL SERTA SOLUSI PENANGGULANGANNYA - zakaria, BAHAUDDIN ZAKARIA (Blueprint Journal, 2025)
Ships are a means of transportation used to transport people or goods. Ships are often used for the needs of transporting large quantities of goods over long distances. One of the factors considered in the ship design process is ship vibration. Vibration is a periodic or repeated movement after a certain time interval called the period. Vibration on the ship is something that has a significant influence on the structural resistance and comfort of the crew. Vibration analysis needs to be carried out to ensure the durability of the ship's construction. Ship construction that is unable to withstand the vibrations it experiences is at high risk of structural failure. Vibration on the ship is also something that can only be dampened and cannot be completely eliminated. The vibrations that occur can cause damage to the ship's structure, components, both machinery and electronics, and can affect the comfort of the crew or passengers.